Mengukur tahap kecekapan perkhidmatan bekalan air di Malaysia: sebelum dan selepas penubuhan Suruhanjaya Perkhidmatan Air Negara (SPAN) dan Perbadanan Aset Air Berhad (PAAB) - Nariman, Mohd Saad (2017)
The regulatory structure of the Malaysian water sector is fairly complex due to the co-existence of a variety of state and federal level water supply institutions that needs a more holistic approach. Thus in 2008, the Federal Government has restructured the water industry and centralized the water management of the state government by establishing SPAN (National Water Services Commission) and PAAB (Water Asset Management Company). The objective of SPAN and PAAB is to improve the efficiency of water operators in Peninsular Malaysia including Labuan. Therefore this study is to measure the level of efficiency of the state’s water services before and after the restructuring, and also determine factors that affect the level of efficiency of the state’s water services. DEA approach (Data Envelopment Analysis), and Malmquist index are used to measure the technical efficiency and productivity of the state’s water supply covering the period 2000-2013 while Tobit model is used to identify factors that contribute to the efficiency score. The result of DEA score show that the sector’s mean technical efficiency through 14 years is about 73%, which means that there is a significant room for improvement and Pulau Pinang state has the most efficient utilization of water and been used as a benchmark for other state in water service. Total Factor Productivity analyses show that the sector lags behind in the area of technological improvements, confirming an ongoing problem of inadequate capital investment. In addition, SPAN and PAAB also need to review their current key performance indicator standards that apply to all state’s water operators. The study also shows that, apart from operating cost, capital cost and revenue of water supply, rate of non-revenue water (NRW) and population density also determine the level of efficiency. Thus each state, should take appropriate measures to reduce NRW level to the national level of 25%, or less, by the year 2020. From consumerism perspectives, state’s water operators should encourage households to use water more wisely or surcharge can be imposed in the event of wasteful water consumption.